Subject-Light Environment as a Platform for Implementation of Universal Design Principles - I. Zhigunova, A.; L. Sokolova, M. (International Journal of Engineering and Technology, 2018)
The present article analyzes the possibility of introducing principles of universal design into the design process of objects, the designs of which provide for the presence of light elements. Compliance with the principles of universal design will allow to fill the environment with more sophisticated design objects that will be convenient and accessible to people regardless of their features. At the same time, the designer often uses a light, or light medium in his work. Light environment can be considered the configuration of light fluxes and objects creating them, transmitting, reflecting and scattering. Such objects can be both of artificial and natural origin. If we consider questions of the interaction of light medium with objects and their aggregates (we can talk both about objects that serve as a source of light and about objects interacting with light), then we can talk about the object-light medium.Â